Effect of biomass characteristics on durability of Cassava stalk residues pellets - Nisanath Kaewwinud; Porntep Khokhajaikiat; Apichart Boonma (Research in Agricultural Engineering, 2018)
This study aims at investigating the effect of the main biomass characteristics (moisture content and particle size) on durability of Cassava stalk residues pellets. This durability is necessary to consider design of the material handling, processing equipment, storage and transportation of biomass pellets. The raw biomass materials were ground and screened into four range sizes and pelletization was done at three different percentage levels of moisture conditions defined as percentage of added water by mass of raw material. Pellets in each condition were analysed for durability. The result showed that the highest durability occurred in particle size 1.7 mm but less than 3.35 mm and 10% moisture content by mass of raw biomass material. The mean durability in the best conditions was 99.02%. This information is important for the design and efficient preparation of biomass material for pelletization to achieve the high quality pellets with high durability for handling, transportation and storage.